Penerapan Pendekatan Teaching at the Right Level (TaRL) untuk Meningkatkan Hasil Belajar Sejarah Peserta Didik - Zahra, Khalishatun; Diansyah, Arfan; Gultom, Imelda M (LPPPI Publishing, 2024)
This research aims to find out how the Teaching at the Right Level (TaRL) approach is implemented as a strategy to improve learning outcomes. TaRL adapts learning to students' level of understanding and encourages problem-based learning. Classroom Action Research (CAR) was conducted at SMAN 14 Medan by applying TaRL. The research method used the Kemmis & McTaggart cycle model consisting of planning, action, observation, and reflection. The research population was students of SMAN 14 Medan, with a sample of grade X-4 students. In cycle I, although there was an increase, the learning outcomes were still not complete. However, in cycle II, there was a significant improvement with 83.33% of students reaching the minimum completion criteria. These results show that the TaRL approach can improve students' understanding of historical material. In addition, the utilization of technology also helps in increasing student participation and expanding the learning resources that students can access. These findings can help education practitioners develop more effective learning strategies that suit students' needs in understanding historical materials.